Minimizing Deviant Workplace Behaviour through Person Job Fit: A Malaysian Case Study - Sathappan, Malini; Adamu, Adamu Abbas (2022)
Recent research has shown that Deviant workplace behaviour is crucial phenomena to be studied. This is due to its consequences on organizations outcomes such as poor performance, low productivity, stress, job dissatisfaction and high turnover among employees. The purpose of this paper is to investigate strategies of deviant workplace behaviour in Malaysia. Data was collected using qualitative approach and a total number of 14 employees from public organization in Malaysia were interviewed. The study found person-job fit as a remedy of deviant workplace behaviour.